1997
DOI: 10.1021/jm960693n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activities of Conformationally Restricted, Tricyclic Nonclassical Antifolates as Inhibitors of Dihydrofolate Reductases

Abstract: Seven novel tricyclic pyrimido[4,5-c][2,7]naphthyridones 5-8 and the corresponding naphthyridines 9-11 were synthesized as conformationally restricted inhibitors of dihydrofolate reductase (DHFR) and as antitumor and/or antiinfectious agents. The analogues were designed to orient the side chain trimethoxyphenyl group in different conformationally defined positions in order to explore the effect of the side chain orientation on binding affinity and selectivity for DHFR from various species. The semirigid orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Though compound 7 was the primary target, we were very much interested in the partially reduced analogues 4 and 6 as well as the essentially planar analogue 5. The varying levels of unsaturation in rings B and C of 4-7 provide subtle variations in the tricyclic ring conformation which provides increased potency and/or selectivity as we have previously reported for the pyrido annulated analogues [26]. In fact, in the tricyclic series 3, the most selective Gangjee et al [28] reported a novel strategy for the synthesis of the tricyclic pyrido [2,3-d]pyrimidines via a Fischer indole type cyclization of a 2-amino-4-oxo hydrazone.…”
Section: Jan-feb 2001 213mentioning
confidence: 79%
See 1 more Smart Citation
“…Though compound 7 was the primary target, we were very much interested in the partially reduced analogues 4 and 6 as well as the essentially planar analogue 5. The varying levels of unsaturation in rings B and C of 4-7 provide subtle variations in the tricyclic ring conformation which provides increased potency and/or selectivity as we have previously reported for the pyrido annulated analogues [26]. In fact, in the tricyclic series 3, the most selective Gangjee et al [28] reported a novel strategy for the synthesis of the tricyclic pyrido [2,3-d]pyrimidines via a Fischer indole type cyclization of a 2-amino-4-oxo hydrazone.…”
Section: Jan-feb 2001 213mentioning
confidence: 79%
“…Gangjee et al [26] recently reported the tricyclic pyrido annulated analogues in which the C5 and N10 were tethered via an ethyl link effectively restricting the 9-10 bridge. Some members of this series of conformationally restricted tricyclic analogues represented by general structure 3 were potent inhibitors of rat liver dihydrofolate reductase with inhibitory constants (IC 50 ) which were highly potent (IC 50 86 nM, for 3 R 1 = 3,4,5-OMePh, R 2 = OH) but the series lacked selectivity for P. carinii or T. gondii dihydrofolate reductase and were in fact much more inhibitory against mammalian dihydrofolate reductase.…”
Section: Jan-feb 2001 213mentioning
confidence: 99%
“…As outlined in Scheme 1, compound 5 was obtained in good yield from 3,3Ј-[(phenylmethyl)imino]bis(propanenitrile) [57,58] after Thorpe intramolecular cyclization using sodium amide in refluxing THF. [59] As for the corresponding ester 3, several strategies to prepare N-acylated or Nalkylated compounds were investigated but all failed, probably for the reasons we evoked in the ester 3 case.…”
Section: Ureido Seriesmentioning
confidence: 99%
“…In that context, several quinoline derivatives have been shown to exhibit high affinity for receptor tyrosine kinases (RTKs), as well as other oncogenic targets, and to possess remarkable antitumor activity both in vitro and in vivo [1][2][3][4][5][6][7] . Many new sulfonamide derivatives, such as HMN-214, E7010 (ABT-751), and E7070 (Indisulam), have shown substantial antitumor activity via different mechanisms as multidrug resistance down-regulation, tubulin polymerization, inhibition of receptor tyrosine kinases (RTKs) among others [8][9][10][11][12][13][14][15][16][17][18][19][20][21] . Recently, the mechanism of sulfonamide antitumor activity has been reported to involve inhibition of carbonic anhydrase (CA) isoforms IX and XII [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Many new sulfonamide derivatives, such as HMN-214, E7010 (ABT-751), and E7070 (Indisulam), have shown substantial antitumor activity via different mechanisms as multidrug resistance down-regulation, tubulin polymerization, inhibition of receptor tyrosine kinases (RTKs) among others [8][9][10][11][12][13][14][15][16][17][18][19][20][21] . Recently, the mechanism of sulfonamide antitumor activity has been reported to involve inhibition of carbonic anhydrase (CA) isoforms IX and XII [19][20][21] . Therefore, in this work, we will prepare some acrylamide containing sulfonamide derivatives and will study their activity against some selected cell lines.…”
Section: Introductionmentioning
confidence: 99%